From the files of Madison Finn: sink or swim - DOWER, LAURA (New York Hyperion, 2003)
12-year-old Madison feels left out when her friends have better summer plans. She takes a babysitting job for a nearby family that turns out to be more difficult than expected, taking her away from her summer fun, friends, and crush, Hart.
English